(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article considers the question of entering the stage of the history of the Islamic community, which is very important in today’s society of Kazakhstan. The factors promoting the development of various cultures in Islamic history are determined. Muslims in the position of power, which led to the separation of the political, legal methodology and results of individual schools, the various problems of reliability, the conditions of the geopolitical situation, regional local specifications, different cultures influence each other, and the philosophical worldview of Muslims in schools, attacks from outside enemies, economic consequences of changing the religious attitudes of the new life, different meanings from verses and hadiths, the existence of different views on traditions, etc. The effect of corridors on the fragment Islam. And the factors that influenced the emergence of Islamic currents that have arisen recently are compared, and their scientific, religious, political and social characteristics are differentiated. The Islamic movements known today in Kazakhstan are classified according to their religious principles, and a new scientific conclusion is made in them. The influence of the Islamic movement in Kazakhstan on the division of society is scientifically analyzed and threatened by the negative impact and threat of unity of the state and society. Key words: islam, prophet, community, mazhab, orden, jamagat, nihla, firka, makalat, ayat, hadis.